The Paradox of Health and Safety Risks: A Disclose of Handling Strategies in Informal Construction Sites in Tanzania - Mwemezi, Benson Rugalema; Kikwasi, Geraldine J.; Phoya, Sarah (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction: Informal construction (IC) involves people working in construction without a license or not under any kind of regulation. Due to its informality, the IC sector suffers from health and safety risk (HSR) handling strategies (HST). This study explored and ranked the HSR HSTs by masonry workers (MWs) in informal construction sites (ICS) in Tanzania. Methods: A total of 10 HSR HSTs were explored from 8 semi-structured interviews, and then, additional data were collected from 304 responses of MWs in ICS through a questionnaire that was formulated from the findings of the interviews. The study employed a sequential exploratory mixed methods approach whereby for qualitative data, direct content analysis was employed followed by quantitative data where descriptive and inferential statistics (one-sample t-tests) were used for analysis. Results: The results show that ‘considering past experience', ‘sitting together and discussing on HSRs', and ‘supervisor's directives' are the most significant ranked HSTs by workers in ICS. In contrast, ‘encouraging other artisans to work together', ‘selling or sub-contracting the work to other artisans', and ‘refusing to take high-risk work so as to avoid a risk' are the least-ranked HSTs. Conclusion: The explored health and safety risk-handling strategies in IC workplaces highlight the need for a health and safety framework in the IC sector using a bottom-up approach. This would help policymakers and practitioners achieve sustainable development goals number three and eight, which promote good health and safety for all, sustainable economic growth, and full and productive employment and decent work for all.